Field-induced antiferroelectric to ferroelectric transitions in (Pb1–xLax)(Zr0.90Ti0.10)1–x/4O3 investigated by in situ X-ray diffraction. Issue 15 (December 2017) - Ciuchi, I.V.; Chung, C.C.; Fancher, C.M.; Guerrier, J.; Forrester, J.S.; Jones, J.L.; Mitoseriu, L.; Galassi, C.
Abstract: Phase transitions and field-induced preferred orientation in (Pb1-x Lax )(Zr0.90 Ti0.10 )1–x/4 O3 (PLZT x/90/10) ceramics upon electric field cycling using in situ X-ray diffraction were studied. The evolution of the 200pc and 111pc diffraction line profiles indicate that PLZT 4/90/10 and PLZT 3/90/10 compositions undergo an antiferroelectric (AFE)–ferroelectric (FE) phase switching. Both PLZT 4/90/10 and PLZT 3/90/10 exhibit irreversible preferred orientation after experiencing the field-induced AFE-to-FE phase switching. An electric field-induced structure develops in both compositions which has a reversible character during the field decreasing in PLZT 4/90/10 and an irreversible character in PLZT 3/90/10. In addition, structural analysis of pre-poled PLZT 3/90/10 ceramics show that it is possible to induce consecutive FE-to-AFE and AFE-to-FE transitions when fields of reversed polarity are applied in sequence. The field range required to induce the AFE phase is broad, and the phase transition is kinetically slow. This kind of transition has rarely been reported before.